ANALISIS RASIO KEUANGAN UNTUK MEMPREDIKSI KONDISI FINANCIAL DISTRESS PERUSAHAAN MENUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2014 - Achmad Tjahjono; Intan Novitasari (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2016)
This study to examine the effect of liquidity to financial distress manufacturing company as measured by current assets, effect of profitability to financial distress manufacturing company as measured by return on assets, the effect of leverage to financial distress manufacturing company as measured by debt ratio, the effect of operating cash flow to financial distress manufacturing company as measured by the operating cash flow divided with current liability. Research population are all manufacturing company that listed in the Indonesia Stock Exchange in 2010-2014. The sampling method in this research is purposive sampling. Samples are 47 companies with as many as 235. The number of observation data analysis method used is logistic regression. The results showed that no effect on the liquidity of financial distress with significant 0.111greather than0.05. Effect on the profitability of financial distress with significant 0.000less than0.05. Leverage does not affect the financial distress with significant 0.167greather than0.05. Operating cash flow does not affect the financial distress with significant 0.875greather than0.05. aximum likelihood on effect simultaneous between liquidity, profitability, leverage and operating cashflow to financial distress with significant 0.000less than 0.05. Koefisient determinasi examination shows value 0.542 that mean 54.2 percentdependent variable can be explained from independent variable and 45.8 percent influenced by other variable outside the model.